(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
Many Byzantine folk-exorcisms take the form of historiolae, i.e. short stories about the victorious confrontation of a saint or an angel with the devil, providing both the mythical foundation and the guarantee of effectiveness of the actual exorcism, often intended to free the “patient”, as well as from the demon, from the diseases caused by it. Sometimes, the historiola ends with a prayer by the holy protagonist, asking and obtaining from God the grant of special blessings for those who will copy the text of the story or will read it aloud, in this way “performing” it. In the case of the so-called “exorcisms of Gello”, some manuscripts have retained the names of the people who had copied the text, or of their family members, literally introduced into the story and into the characters’ dialogues. The most remarkable case, however, is that of a 15th century manuscript of the Testament of Solomon, where an unknown exorcist added his instructions on how to treat the possessed while reading aloud the text. The celebrant repeated on the unfortunate “patient” the same, often violent, actions that Solomon practiced against disease-inducing demons, beating, binding and abusing him in different ways: this provided a kind of performative shock-therapy focused on the re-enactment of the text.